PERSEPSI REMAJA TENTANG TVRI JATIM SEBAGAI MEDIA PENYIARAN PUBLIK LOKAl - Wildani, Muhammad Fawwaz; Dharmawan, Awang (The Commercium, 2024)
The development of information technology and information signifies the progress of mass media, such as television. The television industry in Indonesia has experienced rapid growth, with the emergence of various local to national television stations competing to meet public interests. With digital advancements, teenagers' interest in watching television tends to decline due to the presence of new media platforms with easier access. Adolescents prefer digital content such as social media and streaming videos over watching television, especially considering the presentation of content.Given these issues, the researcher aims to understand teenagers' perspectives regarding public television in the era of social media. This study aims to explore teenagers' perceptions of TVRI as a local public broadcasting media. The concept of perception used in this research is derived from Deddy Mulyana's book, encompassing three processes: sensation, attention, and interpretation. This is a qualitative research study utilizing a case study method. Data collection is obtained through Focus Group Discussions (FGD).The findings of this research indicate that, from the perspective of teenagers, TVRI Jawa Timur's programs still require the development of innovative content to capture their interest. The process of forming perceptions among teenagers aligns with the concept outlined by Deddy Mulyana, involving sensation, attention, and interpretation.